2017
DOI: 10.18052/www.scipress.com/ilshs.76.36
|View full text |Cite
|
Sign up to set email alerts
|

Features of Knowledge Quality of University Students in Ukraine

Abstract: In a highly technological post-industrial society the quality of education is an important factor in providing such a level of life and professional competency of a person that would satisfy both the demands of an individual and the state. The quality of the whole higher education is influenced by the quality of students' knowledge which is acquired at educational classes. Development of studactive classes has brought forward the problem of research of their efficiency, in particular in the aspect of potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Such classes are not only focused on professional interest, they also stand out for progredient active creative individual acquiring competencies by students in coherence with self-reflection, self-improvement, and self-realization, under the influence of collegiality. This research has shown that class efficiency is achieved when the educational, cognitive and creative activity of future engineers exceeds 75% of the academic time (Oleksenko, 2016;Oleksenko, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Such classes are not only focused on professional interest, they also stand out for progredient active creative individual acquiring competencies by students in coherence with self-reflection, self-improvement, and self-realization, under the influence of collegiality. This research has shown that class efficiency is achieved when the educational, cognitive and creative activity of future engineers exceeds 75% of the academic time (Oleksenko, 2016;Oleksenko, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Democracy, the social method of noosphere society, should socially mature and individually mature, creating a proper density of social time -the noosphere epoch. Note that age within 75 years for an individual average developed individual constitutes the peak of personal wisdom development our 2006 generalizations (Oleksenko, 2017;Samodrin, 2019).…”
Section: Control Componentsmentioning
confidence: 99%